Dynamic Quantized Tracking Control for Nonlinear Strict-Feedback Systems Under DoS Attacks and Exogenous Disturbances - Zhao, Can; An, Liwei; Que, Jiaxiong; Wen, Xinluan; Ao, Yucai (IEEE transactions on industrial informatics, 2025)
This article studies the problem of quantized backstepping tracking control for nonlinear strict-feedback systems subject to denial-of-service (DoS) attacks, data rate constraints, and exogenous disturbances. Due to limited network resources, only finite bits of data can be transmitted per time unit. A constant bit encoding-decoding scheme is first designed to guarantee limited data transmissions and be robust to DoS attacks and exogenous disturbances. To reduce the data rate, a variable bit encoding-decoding scheme is further designed that adaptively adjusts the data rate according to the actual frequency and duration of DoS attacks. High-order filters are designed to avoid repeatedly differentiating discontinuous state variables caused by discrete network behaviors in the design of backstepping controller. It is shown that all the closed-loop signals are globally uniformly bounded and the tracking error converges to a neighborhood of the origin. The effectiveness of the proposed scheme is illustrated by the experiment of the wheeled mobile robot.